Loukia Nicolaides, Rising Star - Korae, Eva; Vanezis, Evagoras; Lambrou, Christina (My University, 2025)
Designed as an experiential space for viewing and reflecting on the works of the Cypriot modern painter Loukia Nicolaidou (1909 - 1994), the exhibition "Rising Star, Loukia Nikolaidou", takes place in the house where she was born and raised, at 65 Irinis Street, Lemesos. In this context, a series of events and an intergenerational workshop will be organized, funded by the Toolkit of Care program of the European COST organization. The house holds a position of symbolic movement in the biography of the artist: she left from here in 1929 to study in Paris, returning for a brief period (1933 - 1937) before leaving permanently in 1937 for London. It is in this house that many of the works presented in this exhibition were found in 1987, the "discovery" of which brought attention to the painter and her work. For this project, the house functions as a shell within which a second place unfolds, that of exhibition, an environment of constant interaction of visitors, works, and place. Within the under renovation structure, a temporary structure is erected, designed in collaboration with lovenlight to function simultaneously as both "passage" and meeting place with the works and their stories. The curatorial position approaches the exhibition as a process of production of new knowledge - rather than reproducing or disseminating existing narratives - and focuses on contemporary readings and themes relating to our responsibility towards the heritage of the modern in Cyprus. The artworks are in dialogue with the documentation of their production and the historiography of art. The title “Rising Star” is taken from an article in the newspaper L’ Intransigeant, written on the occasion of Nikolaidou’s participation in the 1932 Salon d'Automne with her painting La Petite Normande (The Young Girl From Normandy). The article was published in translation in the Cypriot newspaper Chronos on March 5, 1933, and reflects an encouraging reception of her work by French critics — in stark contrast to the indifference that her exhibitions faced in Cyprus in the following years, 1934, 1935, and 1936.